Development Policies and Policy Processes in Africa: Modeling and Evaluation - Henning, Christian; Badiane, Ousmane; Krampe, Eva; Henning, Christian; Badiane, Ousmane; Krampe, Eva (Cham Springer Nature, 2017)
economics; quantitative policy evaluation; Comprehensive Africa Agriculture Development Programme (CAADP); poverty
English
Keywords: Politics & government; Development economics & emerging economies; economics; quantitative policy evaluation; Comprehensive Africa Agriculture Development Programme (CAADP); poverty